Problem eating behaviors related to social factors and body weight in preschool children: A longitudinal study - Peterson Kelly; Girard Manon; Farmer Anna; Dubois Lise; Tatone-Tokuda Fabiola (BMC, 2007)
Abstract Background Despite the increasing prevalence of overweight/obesity and its association to eating patterns in adolescents and adults, little is known about the relationship between problematic eating behaviours and body weight in the preschool years within the context of various social factors. This research aims to analyze the relationship between social factors, mothers' perceptions of their child's eating behaviour (picky eating and overeating), and body weight in preschool years, in a population-based cohort of preschoolers from Québec (Canada). Methods Analyses were performed on 1498 children from the Longitudinal Study of Child Development in Québec, a representative sample of children born in 1998 in the Canadian province of Québec. Eating behaviours (picky eating and overeating) were derived from questionnaires at 2.5, 3.5, and 4.5 years of age. BMI was calculated from children's measured height and weight at 4.5 years. Children's sex and birth weight, mothers' age, immigrant status, smoking status during pregnancy, and education level, family type, annual household income and income sufficiency, the number of overweight/obese parents, children's day-care attendance, and food insufficiency were part of the analysis. Multivariate logistic regressions were used to determine odds ratios for different body weight profiles (underweight, normal weight, at risk of overweight, overweight), and one-way analysis-of-variances (ANOVA) allowed for group comparisons of means. Results The proportion of children reported for each eating behaviour category remained quite stable across the years studied. Picky eating and overeating related to body weight among 4.5-year-old children, even when social and parental factors were accounted for in multivariate analysis. Picky eaters were twice as likely to be underweight at 4.5 years as children who were never picky eaters. Adjusted odds ratios revealed overeaters were 6 times more likely to be overweight at 4.5 years than were children who were never overeaters. Conclusion Given the association between eating behaviours and bodyweight among 4.5-year-old children, particularly among those from less educated, lower income families and younger mothers, health professionals should target parents of children at risk of overweight/obesity and underweight with focussed messages and strategies for the management of emerging problematic eating behaviours.